Effect of Grain Modification on Electrical Transport Properties and Electroresistance Behavior of Sm0.55Sr0.45MnO3 - Ibrahim, N.; Azeni Mohamad Rusop, Nur; Rozilah, R.; Asmira, Nor; K.Yahya, A. (International Journal of Engineering and Technology, 2018)
The structural, magnetic, electrical and electroresistance properties of Sm0.55Sr0.45MnO3 manganites sintered at different sintering temperature of 1300oC (S1) and 1400oC (S2) had been investigated for further potential application as a nonvolatile memory elements. The samples were prepared by using conventional solid-state reaction method. An analysis of x-ray diffraction data using Rietveld analysis show that the sample crystalized in orthorhombic structure and formed pure phase. AC susceptibility measurements showed that the magnetic transition temperature remained unchanged as sintering temperature increased indicated heat treatment process does not much influence the magnetic properties of the samples.  Resistivity – temperature curve with different applied currents of 1 mA and 10 mA showed metal-insulator, MI transition temperature, TMI decreased with increased of the applied currents for sample S1.  However, the transition temperature remained unchanged for sample S2. The increased in applied current caused the maximum resistivity around TMI to be decreased  for both samples indicated increased in charge carrier  density which resulting in drop of resistivity, hence, enhanced  double exchange  mechanism. Sample S2 exhibited enhanced in ER effect in the vicinity of M-I transition temperature, TMI compared to S1 sample which may relate to reduction in scattering effect as a result of reduction of grain boundary density. The observation of ER maximum behavior indicated that the materials are suitable for further investigation as a potential device for spintronic applications.
Keywords: Conduction Mechanism; Electroresistance; Grain Modification; Manganites